Etanercept and Methotrexate as Monotherapy or in Combination for Psoriatic Arthritis: Primary Results From a Randomized, Controlled Phase III Trial. Issue 7 (28th May 2019) - Mease, Philip J.; Gladman, Dafna D.; Collier, David H.; Ritchlin, Christopher T.; Helliwell, Philip S.; Liu, Lyrica; Kricorian, Gregory; Chung, James B.
Abstract : Objective: To examine the efficacy of methotrexate monotherapy relative to etanercept monotherapy and the value of combining methotrexate and etanercept for the treatment of patients with psoriatic arthritis (PsA). Methods: In this double‐blind study, 851 patients with PsA were randomized to 1 of 3 treatment arms, as follows: oral methotrexate (20 mg) plus subcutaneous placebo given weekly (n = 284), subcutaneous etanercept (50 mg) plus oral placebo given weekly (n = 284), or subcutaneous etanercept (50 mg) plus oral methotrexate (20 mg) given weekly (combination therapy; n = 283). The American College of Rheumatology 20% improvement (ACR20) response and Minimal Disease Activity (MDA) response at week 24 were the primary end point and key secondary end point, respectively. Other measures of inflammatory arthritis, radiographic progression, and nonarticular disease manifestations were also assessed. Results: Patients with PsA had a mean ± SD age of 48.4 ± 13.1 years, and the mean ± SD duration of PsA was 3.2 ± 6.3 years (median 0.6 years). ACR20 and MDA response rates at week 24 were significantly greater in patients who received etanercept monotherapy compared with those who received methotrexate monotherapy (ACR20, 60.9% versus 50.7% of patients [ P = 0.029]; MDA, 35.9% versus 22.9% of patients [ P = 0.005]), and both were significantly greater in the combination therapy group compared with the methotrexate monotherapy group at week 24 (ACR20, 65.0% versus 50.7% of patients [ P = 0.005]; MDA, 35.7% versus 22.9% of patients [ P = 0.005]). Other secondary outcomes (ACR50 and ACR70 response rates, proportions of patients achieving a Very Low Disease Activity score, and PsA disease activity scores) showed between‐group differences that were consistent with the primary and key secondary end point results. Furthermore, patients in both etanercept treatment arms showed less radiographic progression at week 48 compared with patients who received methotrexate monotherapy. Outcomes were similar in the combination therapy and etanercept monotherapy groups, except for some skin end points. No new safety signals were seen. Conclusion: Etanercept monotherapy and combination therapy with etanercept and methotrexate showed greater efficacy than methotrexate monotherapy in patients with PsA, according to the ACR and MDA response rates and extent of radiographic progression at follow‐up. Overall, combining methotrexate and etanercept did not improve the efficacy of etanercept.